POLITENESS STRATEGIES FOR THE SPEECH ACT OF JOE BIDEN ON CNN - nazira, elsa; Siregar, Fatimah Sari (Al'Adzkiya Journal, 2025)
This research aimed to describe the types of politeness strategies and how politeness strategies are realized by Joe Biden’s speech act when delivering the content of his speech. This research used descriptive qualitative.The data an Source of the data was done collect from https://youtu.be/J5j7OR_IdfM. The data of the research of qualitative method consisted of data collection, data reduction, data display, and conclusion drawing. The approach for analyzing the politeness strategies is based on Brown and Levinson’s Theory of Politeness. There are four politeness strategies that are mentioned by Brown and Levinson, they are Bald on Record, Positive Politeness, Negative Politeness and Off Record. The data of politeness strategies utterances that have been analyzed are 24 utterances which are politeness strategies used in Joe Biden’s speech. The politeness strategies contained in Joe Biden’s speech consist of 4 Bald on Record utterances, 10 Positive Politeness utterances, 8 Negative Politeness utterances, and 2 Off Record utterances.